Mekanisme Insolvency Test Dalam Mencegah Iktikad Buruk Pemailitan Korporasi Oleh Kreditor - Andrian (KRTHA BHAYANGKARA, 2023)
Insolvency Act 37/2004 (UUKPKPU) provides legal alternatives to creditors and debtors to filing bankruptcy or suspension of payment petition. Neither bankruptcy nor suspension of payment petition, debtor has a chance to propose proposals to creditor. Based on article 225 section (3) UUKPKPU, the court is obliged to grant the request for suspension of payment, in maximum of 20 days from the date of application. In suspension of payment process, if proposal is rejected by creditors, then the debtor is declared insolvent. The consequence that occurs when the debtor is declared insolvent from suspension of payment process is that the debtor has no legal remedies, either cassation or reconsideration request. This legal loophole often used by creditors and business competitors to bankrupt the debtor. Thus, an alternative is needed in the form of an insolvency test as the court's authority to check the financial health and sustainability of corporate businesses to prevent intentional bankruptcy by creditors. Regarding the concept of insolvency test and the possibility of implementing this idea, it is necessary to analyze according to the positive law and applicable bankruptcy principles according to UUKPKPU. The author will use the type of normative juridical research with qualitative analysis methods. The analytical approaches that will be used are conceptual approaches, statutory approaches, and historical approaches.